Synthesis & Characterization of Tetrahedrite Compounds for Thermoelectric Applications - (:unkn) unknown (IEEE, 2016)
Thermoelectric materials have attracted much attention due to their potential applications in conversion of heat into electrical power or vice versa to cool the heat-generating elements using electrical power. Tetrahedrite is copper antimony sulfosalt mineral with the formula of CU12Sb4S13, where Cu could be partially replaced by another 3d (Mn, Ag, AI, Cr, Zn, Fe) or other (4d,5d) metal. This group of compounds is very prospective for large-scale thermoelectric applications. The compounds could be represented by common formula of the compound CU(10-x)M(2-x)Sb(4-y)Q(y)S(13-z)Tz. M= Au, Mn, Ag, AI, Cr, Zn, Fe; Q=As, Sn,Zn, Pb; Z=O, Se. The procedure of solid state reaction for tetrahedrite powder samples of various composition have been developed. The single phase tetrahedrite samples of CU12Sb2As2S13, CU11.8Au0.2Sb4S13, and CU10Fe2Sb4S13 have been synthesized as proved by XRD. Characterization of their magnetic properties by VSM PPMS have been done.
Keywords: thermoelectric materials; tetrahedrite; synthesis; FIGURE; MERIT; POWER; STABILITY; NICKEL; HEAT